2016
DOI: 10.3141/2595-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Supervised Classification Techniques for Vision-Based Pavement Crack Detection

Abstract: In this study, the application of four classification techniques for computer vision–based pavement crack detection systems was investigated. The classification methods—artificial neural network (ANN), decision tree, k–nearest neighbor, and adaptive neuro-fuzzy inference system (ANFIS)—were selected on the basis of the complexity and clarity of their procedures. These methods were evaluated for ( a) prediction performance, ( b) computation time, ( c) stability of results for highly imbalanced data sets, ( d) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 19 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…Recently, the automatized acquisition and processing of spatial data on the distortions of roads and runways have been a focus in many studies [28][29][30][31][32][33][34]. In the studies, the authors focused mainly on the interpretation and analysis of road and runway records.…”
Section: Existing Information Models For Monitoring Distortion On Runmentioning
confidence: 99%
“…Recently, the automatized acquisition and processing of spatial data on the distortions of roads and runways have been a focus in many studies [28][29][30][31][32][33][34]. In the studies, the authors focused mainly on the interpretation and analysis of road and runway records.…”
Section: Existing Information Models For Monitoring Distortion On Runmentioning
confidence: 99%
“…Ouma and Hahn [4] constructed an automatic recognition approach of linear cracks based on the wavelet-morphology and circular Radon transform methods. Mokhtari et al [13] utilized artificial neural network (ANN), decision tree, and k-nearest neighbors to classify pavement images into "Crack" and "No Crack" labels; the ANN was proved to be superior to the decision tree and knearest neighbors. Tiled fuzzy Hough transform was applied to detect near straight segments of cracks embedded in pavement textures [14]; this study confirms that the fuzzy Hough transform is effective in diminishing the contribution of texture and noise pixels.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Rababaah [26] carried out a comparative work which investigated the performance of multilayer perceptron neural network, genetic algorithms, and self-organizing maps in pavement crack classification. Mokhtari et al [27] recently employed neural network models to tackle the problem of interest; this study concluded that neural network models are more capable than other learning strategies of decision tree and knearest neighbor. Banharnsakun [28] combined the advantage of metaheuristic and neural network for pavement surface distress detection and classification; the metaheuristic of artificial bee colony was used in the phase of image segmentation, and the subsequent classification task was performed by neural network.…”
Section: Introductionmentioning
confidence: 97%